Innovation Of Islamic Religious Education (PAI) Teaching Materials Based On Lks And Its Implications For Learning At Mas Darul Muqomah Al-Khoiriyyah - Jaka Hadi Wijaya; Joko Susilo Rusnan; Saiful Bahri; Maya Sari (International journal of technology and education research, 2026)
Learning Islamic Religious Education (PAI) in madrasas is still often face problematic Serious in the form of use teaching materials Worksheets Students (LKS) which are of a nature conventional, good from aspect monotonous visual design, shallow and uninteresting content contextual with life students, as well as approach pedagogical which only memorization - oriented cognitive level low. Research This aim For develop and implement innovation contextual LKS -based Islamic Education teaching materials with characteristics Islamic boarding school as well as analyze the implications to learning. Type research used is qualitative with approach studies field, involving three Islamic Education teachers and two twelve MAS Darul students Muqomah Al- Khoiriyyah as data sources, with technique data collection through observation participatory, interview in-depth, and documentation. Research results show that the LKS that has been This used own significant multidimensional weaknesses. The process of developing innovative LKS done in a way participatory through FGD and validated by experts materials, media, and culture Islamic boarding school until declared very feasible. Implementation of innovative LKS succeed transform dynamics class from passive become collaborative, improving motivation and independence Study students, as well as push occurrence deep personal reflection. Implications positive seen in the third dimensions learning, namely improvement ability analysis critical, change attitude more social and spiritual positive, and ability student in carry out project action real based Islamic values. In conclusion that contextual and participatory PAI LKS innovation own Power significant transformation to quality learning. Implementation results study This push the need adoption of innovative LKS in a way area, teacher training, and support madrasah policy for ensure sustainability innovation.